2011
DOI: 10.1126/science.1207079
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Acetylcholine Receptor β2 Subunits in the Medial Prefrontal Cortex Control Attention

Abstract: More than one-third of all people are estimated to experience mild to severe cognitive impairment as they age. Acetylcholine (ACh) levels in the brain diminish with aging, and nicotinic ACh receptor (nAChR) stimulation is known to enhance cognitive performance. The prefrontal cortex (PFC) is involved in a range of cognitive functions and is thought to mediate attentional focus. We found that mice carrying nAChR β2-subunit deletions have impaired attention performance. Efficient lentiviral vector-mediated reexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
146
2
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(162 citation statements)
references
References 28 publications
7
146
2
7
Order By: Relevance
“…It has been reported that the β2 subunit is involved in the dendritic morphogenesis of pyramidal neurons, and in particular, in the circuits that contribute to the high-order functional connectivity of the cerebral cortex (40). These defects in the maturation of the cerebral cortex that have been reported in the β2 KO mice could contribute to the observed behavioral deficits (4,13,16). However, our data reveal that pharmacological intervention with nicotinic antagonists is enough for the disruption of USF mechanisms.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…It has been reported that the β2 subunit is involved in the dendritic morphogenesis of pyramidal neurons, and in particular, in the circuits that contribute to the high-order functional connectivity of the cerebral cortex (40). These defects in the maturation of the cerebral cortex that have been reported in the β2 KO mice could contribute to the observed behavioral deficits (4,13,16). However, our data reveal that pharmacological intervention with nicotinic antagonists is enough for the disruption of USF mechanisms.…”
Section: Discussioncontrasting
confidence: 53%
“…Importantly, lesions of the prelimbic cortex (PrLC) in WT mice cause deficits in social behavior, similar to those observed in β2 knock-out (KO) mice, whereas re-expression of the β2 subunit in the PrLC of β2 KO mice rescues their social interaction (4). Similarly, re-expression of β2 subunits in the PrLC of β2 KO mice fully restored their attentional performance in the five-choice serial reaction time task (16).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…This study showed that lesions of the mPFC, forebrain structures involved in awareness formation [31][32][33] , induce deficits in acquisition of the CR with a soft-tone CS, but not a loud-tone CS [30] . While the concept of conscious knowledge is not readily applicable to experimental animals, it is believed that the critical element that confers awareness about acquired knowledge comes from the conjoint operation of the neocortex and the hippocampal system [11] .…”
Section: Discussionmentioning
confidence: 70%
“…Although the latter study does not address the involvement of a4b2 nAChRs, clinical trials investigating a4b2 agonists in disorders displaying attentional deficits, for example attention-deficit/hyperactivity disorder (ADHD), have shown promising results [32,33]. Additionally, b2 knockout mice have demonstrated attentional deficits in the five-choice serial reaction time task, which can be completely rescued upon selective re-expression of b2* nAChRs in the mPFC [34].…”
Section: Molecular Aspects Of Nachrsmentioning
confidence: 99%